Salinity management under a trickle irrigation system - Rafeet, Mohamed Ali, author; Podmore, T. H., advisor; Cardon, G., advisor; Oad, R., committee member; Davis, J., advisor; Unidentified committee member (Colorado State University. Libraries, 2002)
The aim of this study was to investigate the effects of trickle (drip) irrigation management under saline conditions on sweet com. The study concentrated on two main factors: amounts of irrigation water and irrigation frequency, either in the field or the Hydrus -2D model. The study objectives were to determine the optimum irrigation configuration to reduce the hazards of salinity in order to increase crop production and to use the model to predict the optimal trickle irrigation management for sweet com and other row crops. To reach these objectives, measurement data from an experimental field was compared with data from the model based on the field conditions. Additionally, water use efficiency (WUE) and relative yield (RY) were investigated.

The study area was 820 m2 irrigated by a trickle irrigation system at the Horticultural Experimental Station in northeast Fort Collins, Colorado. The experiments were carried out for two growing seasons (1999 and 2000). The irrigation water application rates were 100%ET, 116%ET, and 124%ET during the 1999 growing season with 3 and 7 day intervals between the irrigations, and 100%ET, 115%ET, and 130%ET during the 2000 growing season with 2 and 7 day intervals between the irrigations. During the growing season, soil samples were taken from different depths under the emitters and midway between the emitters. The soil samples were taken three times: at the beginning, mid-season, and the end of the season immediately after harvest to estimate electrical conductivity in the active root zone. Salt accumulations simulated by the model for the same field conditions at the same depths were compared with field measurements. Therefore, 72 additional treatments were simulated by the model to estimate the ratios of actual transpiration and potential transpiration (Ta/Tp). From these ratios, expected relative yield (RY) was calculated.

The field results indicated that the greatest amount of accumulated salt occurred under deficit (100%ET) irrigation treatments, and the lowest level of accumulated salt tended to occur under the highest amounts of irrigation water treatments for both seasons. However, thelOO%ET treatments produced the greatest values of WUE, whereas, the 116%ET and 115%ET resulted in the highest values of RY for both seasons. In general, good agreement between the observed and simulated data on salt distribution was found under the small spaces between the emitters and laterals. Even greater agreement occurred vertically under the emitters compared with the horizontal direction midway between the emitters and lateral tubes. In the simulated treatments simulated using the model, the model produced the greatest values of Ta/Tp and RY under short term irrigation intervals compared with longer irrigation interval. The closer the space between the emitters, the greater the values of Ta/Tp and RY.
Keywords: agricultural engineering; civil engineering